Ocuparea pe platformele digitale în contextul crizei COVID-19: Studiu de caz asupra personalului de livrare - Bădoi, Delia (Calitatea Vieții, 2020)
The article intends to critically analyse the implications of economic precariousness integrated into the platform work of food-delivery sector. The recent context of labour market crisis caused by the COVID-19 virus and assisted by the labour policy changes have brought recently on the public agenda the subject of digital employment. However, at the academic level, this subject has been sporadically analysed, marginalizing the dimensions related to the risks and vulnerabilities associated with the precarization effect on digital work. Therefore, by combining different analytical angles, focusing on the socio-economic conditions and vulnerability of workers from the food-delivery sector, the article aims a synthetic analysis of the association between precarious work, the accelerated digitization of work caused by COVID-19 and the phenomenon of flexible employment. Thus, there are two approaches in the proposed article demonstration: first, the article will provide information on the political and economic context of the Romanian labour market before the COVID-19 pandemic crisis and will present the current situation of precarious employment and minimum wage policy. Secondly, the analysis will be focused on digital employment in the platform-based food-delivery sector in Romania, with a case study on the delivery staff situated in the first line exposure to the COVID-19 virus.